Effect of Press Cycle Time on Application Behavior of Board Made from Chemically Modified Particles - Fatemeh Bavaneghi (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Although acetylation is effective in achieving high hydrophobicity, dimensional stability, and decay resistance of particleboards, springback and mechanical strength loss in modified boards should be improved to maintain high performance of this method. It is questioned if acetylation, due to the hydrophobic nature of modified flakes, could interfere with the polymerization reaction of the phenolic resin. In this research, the effect of different press durations on bioresistance, physical and mechanical behavior of acetylated particleboards at various weight percent gains (WPG) was investigated. Results showed that acetylated boards possessed very low moisture content, water absorption, thickness swelling and biological degradation values compared to control boards. Increasing press time intensified reduction in these boards, with the exception in untreated boards. Also acetylation resulted in high correlation between the springback and the strength losses of the boards due to weak bonding between the wood flakes. Prolongation of the press time in the acetylated boards caused significant reduction in springback and mechanical loss. Regarding the outdoor use with biological degradation for modified boards, an increase in the press time for improving these properties might be recommended.